A critical analysis on Brazilian computational scientific events linguistic aspects - Carvalho, Luiz Paulo; Bim, Sílvia Amélia; Santoro, Flávia Maria; Oliveira, Jonice (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
Among the various ethical or moral aspects of the research, one is the choice of language for scientific communication. The publication language choice can exclude or include people in effective communication, which makes us reflect on its social function, and its moral justifications. The two most common languages in the Brazilian scientific context are Brazilian Portuguese and English. We present a critical, dialectical and bilingual ethical essay, evidenced in data and phenomena of materiality, to discuss the linguistic panorama of Brazilian computing scientific events. We perceive a strong call for internationalization, accompanied by an "Englishfication" of the events. Certain Brazilian academic areas of computing are restricted exclusively to English. In others, Brazilian Portuguese predominates, even open to English. The excerpt in Brazilian Portuguese opens this work, followed by the excerpt in English.